close
標題:
此文章來自奇摩知識+如有不便請留言告知
form 2 Maths
發問:
Make x the subject of the equation y=4x-3 over 2x+1
最佳解答:
y = (4x-3) / (2x+1) y (2x+1) = 4x -3 2xy + y = 4x-3 y+3 = 4x - 2xy y+3 = x (4-2y) x = (y+3) / (4-2y) =)
其他解答:
y = (4x - 3)/(2x + 1) y(2x + 1) = 4x - 3 2xy + y = 4x - 3 4x - 2xy = y + 3 x(4 - 2y) = (y + 3) x = (y + 3)/(4 - 2y)|||||y(2x+1)=4x-3 2xy+y=4x-3 2xy+y+3/4=x x=2xy+y+3/4 2006-10-22 23:22:07 補充: 2xy+y=4x-34x-2xy=y-3x(4-2y)=y-34-2y/y-3=x|||||y ( 2x+1) = 4x -3 2xy + y = 4x-3 4x-2xy = y+ 3 x ( 4-2y )=y+3 x= y+3 over 4-2y
文章標籤
全站熱搜